Uma retórica a serviço da morte e da vida: estudo de um idioleto de background metafórico e metonímico no cinema de Stanley Kubrick - Carvalho, Caio M. G. de (2018)
Based on the filmography of the director Stanley Kubrick (short-films excluded), the present work focuses on exposing and analyzing a framework of intertextual relations (our empiric object) which are established movie-by-movie, from the point where it is allowed to suppose a metaphoric code through Kubrick’s filmography. It was aimed to demonstrate how this intertextual network reveals an ‘own’ Kubrickian code (defined as idiolet in his filmography), by gathering the filmmaker’s thirteen full-length movies (our study corpus) and correlating them to several metaphorical amalgams with the <<death>> sememe. It is defined as ‘intertext’ the different matching relations of content between equal (as in film-to-film) or different (as in a film to a strictly verbal text) semiotic systems – which permitted us to consider this concept as a synonym of ‘intersemiotics’, which its base of functioning lies in the umbertian definition of ‘sign-function’ (our number 1 epistemological object). At the end of the display of this intertextual network (or intersemiotics), it has been pursued a critical interpretation in relation to what this idiolet can tell us about Stanley Kubrick’s cinema. Therefore, it is proposed – under the optics of metaphor (our number 2 epistemological object) and the intertext it establishes in the filmmaker’s work – different forms to address the North-American director’s filmography. The theoretic-methodological basis is guided by Umberto Eco’s semiotics – a theorist who has always shown commitment to study mechanisms which impose, allow (and that also limit, one could say) the different levels of reading offered through the result of any aesthetical use of language, such as film or literature. This work is also based on informed readings about cinema, and of course, Stanley Kubrick’s cinema as well